Russia's influence operations in the Czech Republic during the radar debate. Issue 2 (3rd March 2020) - Dodge, Michaela
Abstract: The article highlights Russia's influence operations in the Czech Republic during U.S.-Czech ballistic missile defense discussions and negotiations between 2002 and 2011. Russia's influence operations are an example of its first successful effort on a new North Atlantic Treaty Organization member state territory. They are significant because Russia will use similar approaches in other states and the United States must understand them before it can successfully counter them. This is a first public comprehensive effort to map them in connection to U.S.-Czech radar negotiations and draw conclusions for U.S. and allied foreign and defense policies.